Metástases de carcinoma de mama em cadelas: avaliação da técnica de linfonodo sentinela - Beserra, Hugo Enrique Orsini [UNESP] (2014)
Microscopic evaluation of lymph nodes in bitches with mammary carcinomas may have fundamental importance in guidance the therapy since lymphatic drainage constitutes the most common route for metastasis. In recent years, several techniques have been used to detect and remove Sentinel Lymph Nades (SLN) based on the principIe of stepwise progression of cancer and lymphatic drainage. In human medicine, SLN biopsy and analysis constitutes the main prognostic factor in women with mammary , carcinomas. This study was designed to evaluate, in an unprecedented manner, the accuracy of sentinel lymph no de biopsy in bitches with mammary carcinomas. Forthyone dogs with no predilection for breed or age, with previous cytological diagnosis of mammary carcinoma were submitted to inoculation of patent blue V dye in peritumoral skin, followed by radical mastectomy and radicallymphadenectomy. Lymphanedectomy included sentinel and non- sentinel lymph nades in order to detect lymph nade metastasis. Both groups were compared in order to determine the accuracy of SLN technique in the detection of node metastasis. The lymph nades were subject to a standard serial sectioning method, stained by routine H&E or submitted to immunohistochemistry using pan-cytokeratins AEl/AE3 and the myoepitelial marker CK14. Nineteen animaIs (46.3%) had nodal metastasis. Sensibility and specificity for SLN technique were 89.5 % and 100 %, respectively, with a kappa value of 0.90 (p<O.OOOl). Therefore, SLN biopsy offers high sensitivity in the early diagnosis of lymph no de metastasis allowing a more accurate clinical staging. These results probably impacts on greater chances of patient survival